If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z+43/10=6
We move all terms to the left:
z+43/10-(6)=0
determiningTheFunctionDomain z-6+43/10=0
We multiply all the terms by the denominator
z*10+43-6*10=0
We add all the numbers together, and all the variables
z*10-17=0
Wy multiply elements
10z-17=0
We move all terms containing z to the left, all other terms to the right
10z=17
z=17/10
z=1+7/10
| -4a-4=7/4a-3 | | 63=9(t-85) | | m/6+31=33 | | x=x5+78 | | 6+7=s | | 11=8n-15 | | y-36/4=10 | | 6+7=g | | 70=7(r+1) | | 8+7=k | | -74=-6c+-8 | | 2x^2+9x-5=) | | X=10x-7 | | 2u—2=26 | | 147÷n=21 | | 132/p=-12 | | -21.95=-3.6m-1.07 | | X=5x+78 | | w/3+10=18 | | 12=j+6 | | 3x+4=2x=27 | | 123/x=-12 | | 12=j6 | | 16=20-2u | | H=5+75t-16t2 | | 5x-61+64=180 | | -24=-4(-2k-3) | | -x=2=x-14 | | 7e−4=38 | | 18h+13h=31h | | 9x-6x+10=43 | | -9+3x=-8,1 |